Los dos cuchillos pontificio y regio: un difícil equilibrio en tiempos de calamidad en el Perú virreinal (segunda mitad del siglo XVII) - Yasmina Rocío Ben Yessef Garfia (Nuevo mundo - Mundos Nuevos, 2022)
The expression dos cuchillos was used by the Augustinian regalist bishop Gaspar de Villarroel in his work Govierno eclesiástico pacífico y unión de los dos cuchillos, pontificio y regio (published in two volumes in Madrid in 1656 and 1657). Even if the attempt was to establish the foundations for a happy coexistence and collaboration between Church and State, this text does not ignore more or less veiled criticisms of the excesses of the Hispanic Monarchy’s ministers towards ecclesiastical institutions. Indeed, the relations between these two institutions in this period were characterized by great uncertainty. The analysis of calamitous events such as, for example, the earthquakes that occurred in those years in the Viceroyalty of Peru, constitutes an excellent perspective to understand the difficult relationship established between the ecclesiastical and secular agents. Through the study of the documents produced by both, it is possible to deduce: the definition of the earthquake as God's punishment by the Church's agents for the defense of the ecclesiastical jurisdiction; the different interests of these figures; and finally, the conflicting relationships entertained between the Church and the State in the second half of the seventeenth century.